2019
DOI: 10.1093/mnras/stz484
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the line width of the atomic and molecular ISM in M33

Abstract: We investigate how the spectral properties of atomic (H I) and molecular (H 2 ) gas, traced by CO(2-1), are related in M33 on 80 pc scales. We find the H I and CO(2-1) velocity at peak intensity to be highly correlated, consistent with previous studies. By stacking spectra aligned to the velocity of H I peak intensity, we find that the CO line width (σ HWHM = 4.6 ± 0.9 km s −1 ; σ HWHM is the effective Gaussian width) is consistently smaller than the H I line width (σ HWHM = 6.6 ± 0.1 km s −1 ), with a ratio o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 63 publications
3
15
0
Order By: Relevance
“…Approximating the disc as a uniform exponential disc, the power spectrum should have a break near the disc scale length 4 and a flat power spectrum on larger scales. While this is a plausible explanation for the CO(2-1) power spectrum from Combes et al (2012) (see Koch et al 2019b), this simple model does not explain the lack of a power spectrum break near the disc scale length nor the shallow power spectrum measured for the dust surface density and IR bands. This implies that the more diffuse and predominantly atomic gas plays an important role in setting the large scale power spectrum shape.…”
Section: Variation In the Power Spectrum Index Between Galaxiesmentioning
confidence: 82%
See 2 more Smart Citations
“…Approximating the disc as a uniform exponential disc, the power spectrum should have a break near the disc scale length 4 and a flat power spectrum on larger scales. While this is a plausible explanation for the CO(2-1) power spectrum from Combes et al (2012) (see Koch et al 2019b), this simple model does not explain the lack of a power spectrum break near the disc scale length nor the shallow power spectrum measured for the dust surface density and IR bands. This implies that the more diffuse and predominantly atomic gas plays an important role in setting the large scale power spectrum shape.…”
Section: Variation In the Power Spectrum Index Between Galaxiesmentioning
confidence: 82%
“…In M33, the H 2 distribution is centrally-concentrated in the galaxy and primarily from GMC scale emission (Rosolowsky et al 2003). Koch et al (2019b) show that the distribution of GMCs in M33 can provide an excess in power on scales up to ∼ 2 kpc, and can therefore affect the CO and dust power spectra shape on similar scales. The final fourth point will tend to flatten the dust power spectrum on large scales, as the dust abundance decreases with metallicity.…”
Section: Comparisons With H I and Co Power Spectramentioning
confidence: 87%
See 1 more Smart Citation
“…However, it is important to acknowledge that there are also cases where no evidence for a significant thick CO component has been found (e.g., M33; Koch et al 2019), and that we are still missing an extensive investigation of the frequency and properties of CO diffuse, thick discs, primarily due to the lack of CO observations able to trace emission at all physical scales. Moreover, it remains unclear if the fraction of diffuse CO emission maps directly into diffuse H 2 or not, which would clearly impact the overall physical scenario of direct molecular hydrogen stripping.…”
Section: What About Molecular Hydrogen?mentioning
confidence: 99%
“…moments maps, position-velocity diagrams, rotation curves) in Appendix A. In B19a, we did not analyse the molecular gas kinematics for each galaxy in the sample, as we relied on previous works in the literature that showed that the velocity dispersion of CO is about half of σ HI (Mogotsi et al 2016;Marasco et al 2017;Koch et al 2019). For this work, a robust measurement of the velocity dispersion is desirable to accurately calculate Eq.…”
Section: Molecular Gas Distribution and Kinematicsmentioning
confidence: 99%